2014
DOI: 10.1089/neu.2013.3216
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal White Matter Changes after Traumatic Axonal Injury

Abstract: Diffusion tensor imaging (DTI) has been useful in showing compromise after traumatic axonal injury (TAI) at the chronic stage; however, white matter (WM) compromise from acute stage of TAI to chronic stage is not yet well understood. This study aims to examine changes in WM integrity following TAI by obtaining DTI, on average, 1 d post injury and again approximately seven months post-injury. Sixteen patients with complicated mild to severe brain injuries consistent with TAI were recruited in the intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
(77 reference statements)
2
29
0
Order By: Relevance
“…In a study of 12 Iraq/Afghanistan veterans, the blast-exposed group showed hypermetabolism in some frontal cortex but showed hypometabolism in the right superior parietal region and deficits on the paced auditory addition test compared with controls (Mendez et al, 2013). Moreover, other studies are finding that long-term changes to the diffusivity of axons can be seen at 7 months following a TBI, echoing observations of changes in axonal diffusivity (Perez et al, 2014). Behaviorally, changes to emotionrelated brain regions such as the amygdala can result in expression of PTSD-like symptoms.…”
Section: Does Blast Exposure Produce Morphological Changes Similarmentioning
confidence: 93%
“…In a study of 12 Iraq/Afghanistan veterans, the blast-exposed group showed hypermetabolism in some frontal cortex but showed hypometabolism in the right superior parietal region and deficits on the paced auditory addition test compared with controls (Mendez et al, 2013). Moreover, other studies are finding that long-term changes to the diffusivity of axons can be seen at 7 months following a TBI, echoing observations of changes in axonal diffusivity (Perez et al, 2014). Behaviorally, changes to emotionrelated brain regions such as the amygdala can result in expression of PTSD-like symptoms.…”
Section: Does Blast Exposure Produce Morphological Changes Similarmentioning
confidence: 93%
“…In a different TBI study, a proportional increase in AxD and RD without a significant change in FA at the acute stage (within 1-3 days) was followed by a disproportionate increase in AxD and RD in conjunction with a decrease in FA at the chronic stage (after 7 months) in patients (25). Early post-injury changes in RD were suggested to be a biomarker of oedema and demyelination (25). Song et al specifically explored the potential of AxD and RD as biomarkers of axonal damage and myelin degeneration in a mouse model of retinal ischemia (3).…”
Section: Introductionmentioning
confidence: 90%
“…This was concluded based on previously published histological findings on axonal swelling, damage, and recovery (24). In a different TBI study, a proportional increase in AxD and RD without a significant change in FA at the acute stage (within 1-3 days) was followed by a disproportionate increase in AxD and RD in conjunction with a decrease in FA at the chronic stage (after 7 months) in patients (25). Early post-injury changes in RD were suggested to be a biomarker of oedema and demyelination (25).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment partly derives from a lack of structural and trophic support from OLs to axons, which fail to adequately remyelinate, thereby leading to axonal degeneration and disease progression [77]. In traumatic brain injury (TBI), myelin plasticity and remodeling influence recovery of WM integrity and resynchronization of cortical circuits [78,79]. Further, microstructural WM damage sustained during TBI can have lasting effects on cognition [80], behavior [81], and increase susceptibility to psychiatric [82] and neurodegenerative disorders like Parkinson’s disease [83].…”
Section: Myelin Plasticity Throughout Lifementioning
confidence: 99%